Angiotensin II-mediated neuroinflammation in the hippocampus contributes to neuronal deficits and cognitive impairment in heart failure rats - Althammer, Ferdinand; Roy, Ranjan K.; Kirchner, Matthew K.; Campos-Lira, Elba; Whitley, Kathryn E.; Davis, Steven; Montanez, Juliana; Ferreira-Neto, Hildebrando Candido; Danh, Jessica; Feresin, Rafaela; Biancardi, Vinicia Campana; Zafar, Usama; et al. (Hypertension, 2023)
Background: - Heart failure (HF) is a debilitating disease affecting >64 million people worldwide. In addition to impaired cardiovascular performance and associated systemic complications, most patients with HF suffer from depression and substantial cognitive decline. Although neuroinflammation and brain hypoperfusion occur in humans and rodents with HF, the underlying neuronal substrates, mechanisms, and their relative contribution to cognitive deficits in HF remains unknown. - Methods: - To address this critical gap in our knowledge, we used a well-established HF rat model that mimics clinical outcomes observed in the human population, along with a multidisciplinary approach combining behavioral, electrophysiological, neuroanatomical, molecular and systemic physiological approaches. - Results: - Our studies support neuroinflammation, hypoperfusion/hypoxia, and neuronal deficits in the hippocampus of HF rats, which correlated with the progression and severity of the disease. An increased expression of AT1aRs (Ang II [angiotensin II] receptor type 1a) in hippocampal microglia preceded the onset of neuroinflammation. Importantly, blockade of AT1Rs with a clinically used therapeutic drug (Losartan), and delivered in a clinically relevant manner, efficiently reversed neuroinflammatory end points (but not hypoxia ones), resulting in turn in improved cognitive performance in HF rats. Finally, we show than circulating Ang II can leak and access the hippocampal parenchyma in HF rats, constituting a possible source of Ang II initiating the neuroinflammatory signaling cascade in HF. - Conclusions: - In this study, we identified a neuronal substrate (hippocampus), a mechanism (Ang II-driven neuroinflammation) and a potential neuroprotective therapeutic target (AT1aRs) for the treatment of cognitive deficits in HF.
Gesehen am 21.09.2023